Chemical composition of regenerated bone tissue under effect of EasyGraft and amorphous calcium phosphate implants. - Dmitriyeva E. А. (Морфологія / Morphologia / Morfologìâ, 2011)
In this study we investigated the effects of EasyGraft and amorphous calcium phosphate implanted into the proxymal metadiaphysis on bone regeneration and cancellous bone within reaction zone. Here we found out that EasyGraft and amorphous calcium phosphate undergo resorbtion and thus optimize bone regeneration. Regeneration is accompanied by dysbalance of regenerate chemical composition which is levelled. Highest intensity of these processes was ob-served in the period from 7th fill the 30th day after implantation. EasyGraft is more preferable for implantation than amorphous calcium phosphate.